3D printing for advanced surgical planning in veterinary medicine—case studies, methods and future perspectives - Lima, Ramon Rodrigues de; Carvalho, Lucas Rannier Ribeiro Antonino (Frontiers in Veterinary Science, 2025)
IntroductionConventional surgical planning in veterinary medicine is based on two-dimensional imaging, while advanced planning incorporates technologies such as three-dimensional reconstruction and virtual simulations. 3D printing has emerged as a promising tool, providing greater precision and customization of surgical procedures. The objective of the study is to analyze the applicability of 3D technology for surgical planning in veterinary medicine.MethodsThe physical model is materialized using different techniques, such as stereolithography (SLA), selective laser melting (SLM), and fused deposition modeling (FDM), the latter being the most accessible and used in this report. To construct the digital models, the CT data are processed using inVesalius 3.1 software, a Brazilian program for segmentation and rendering of medical images. The resulting model is exported in .stl format and refined using Blender® software. The final printing is performed using the FDM method, using a slicer software, such as Ultimaker Cura®, which converts the 3D model into layers and generates commands for the printer. This process allows greater control over parameters such as temperature and speed, ensuring precision in the production of physical models.ResultsFive different cases using 3D technology for surgical planning in dogs were described. In the first three cases, complete skulls were printed for oncological and temporomandibular joint (TMJ) surgery; in the last cases the areas of surgical interest were portions of the spinal column, the atlantoaxial region, and the thoracolumbar vertebrae.Conclusion3D printing has been gaining ground in veterinary medicine, becoming a valuable tool in surgical planning and simulations. Even with the known relevance of new 3D technologies, more studies are needed in the development of new available materials, combination of techniques, accessibility, and medical education for the use of new applications and possibilities of 3D printing.